Effects of annual training cycle on the metabolic response to supra-maximal exercise test in beach volleyball players - Pilaczynska-Szczesniak, L.; Lisiecki, D.; Kasprzak, Z.; Karolkiewicz, J.; Sliwicka, E.; Nowak, A.; Podgorski, T.; Lewandowska, M. (Journal of Human Kinetics, 2011)
The aim of this study was to analyze the effects of sports training on the physiological response to supra-maximal exercise during consecutive phases of the annual training cycle. The study was carried out in volleyball players at the onset of each training phase. VO2 max was determined by an indirect method using the Ästand-Rhyming nomogram and biochemical analyses were performed before and after the Wingate test. Concentrations of lactate in capillary blood were measured and levels of glucose, insulin, visfatin, resistin, thiobarbituric acid reactive substances (TBARS) of serum and the total antioxidative status of plasma were determined using venous blood. Most significant differences with respect to physiological and biochemical variables centered around the precompetitive phase when compared to other phases of the annual training cycle. Blood visfatin concentration in highly trained volleyball players is reduced by supra-maximal exercise, whereas levels of resistin remain relatively constant at rest. With the exception of the competitive phase, values of the insulin resistance index fit within the reference range. Levels of lipid peroxidation products were inversely correlated with the insulin resistance index and resistin concentrations. The physical training during the annual cycle does not affect resistin levels, but influences insulin, glucose and visfatin concentrations, along with markers of pro-oxidant/antioxidant balance in beach volleyball players.